2014
DOI: 10.3767/000651914x684376
|View full text |Cite
|
Sign up to set email alerts
|

A revision of <I>Cenchrus</I> incl. <I>Pennisetum</I> (<I>Gramineae</I>) in Malesia with some general nomenclatural notes

Abstract: InTRoduCTIonCenchrus L. s.s. (Gramineae) long has been regarded as closely related to Pennisetum Rich., differing mainly by the usually retrorsely barbed bristles at least basally connate and the chromosomal allopolyploid base number x = 17 (8 + 9). Donadio et al. (2009) found that Cenchrus is nested in Pennisetum. Morrone in Chemisquy et al. (2010) made the 'necessary' new combinations in Cenchrus, apparently more induced by the molecular 'evidence' than the nomenclatural stability of the majority of the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
0
12
0
6
Order By: Relevance
“…3). Previously, different studies revealed the close relationship between Cenchrus and Pennisetum and the merge of Pennisetum to Cenchrus was also suggested (Chemisquy et al, 2010; Veldkamp, 2014). In this study, the relationship between Pennisetum and Cenchrus was not checked due to the lack of complete cpDNA sequences of Pennisetum .…”
Section: Discussionmentioning
confidence: 99%
“…3). Previously, different studies revealed the close relationship between Cenchrus and Pennisetum and the merge of Pennisetum to Cenchrus was also suggested (Chemisquy et al, 2010; Veldkamp, 2014). In this study, the relationship between Pennisetum and Cenchrus was not checked due to the lack of complete cpDNA sequences of Pennisetum .…”
Section: Discussionmentioning
confidence: 99%
“…Based on Cope (1994), Veldkamp (2014) and Clayton (1980), we suggest a new key for the identification of Pennisetum species presents on Madeira archipelago.…”
Section: Methodsmentioning
confidence: 92%
“…Pennisetum clandestinum, was included in a separate genus -Kikuyuochloa H. Scholz (Scholz, 2006), but included in Cenchrus by other authors (Verloove 2012;Veldkamp 2014). The taxonomic and nomenclatural criteria adopted here follow Jardim and Menezes de Sequeira (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The type material of Panicum triticoides Poir. (Poiret 1816: 274) has still not been located following the search last conducted by Veldkamp (2014)…”
Section: Usesmentioning
confidence: 99%
“…are both ecologically significant across the tropics, characterised by bristles surrounding and subtending each spikelet, the whole structure deciduous as a unit (Clayton & Renvoize 1986). It has become increasingly clear that traditionally delimited Cenchrus originated from within Pennisetum, and both are now placed in the expanded genus Cenchrus in the Poaceae subfamily Panicoideae, tribe Paniceae, subtribe Cenchrinae (Chemisquy et al 2010;Veldkamp 2014;Kellogg 2015;Soreng et al 2017). Ten species of the united genus Cenchrus are listed for Madagascar by Bosser (1969), not including the cultivated crop pearl millet Cenchrus americanus (L.) Morrone (formerly Pennisetum glaucum (L.) R.Br.).…”
Section: Introductionmentioning
confidence: 99%